PENGARUH PENDIDIKAN MULTIKULTURAL TERHADAP SIKAP TOLERANSI SISWA DI UPT SPF SD INPRES ANTANG 1 KOTA MAKASSAR - Novianti; Bellona Mardhatillah Sabillah; Eka Fitriana HS; Nurhadifah Amaliyah (LPPM Universitas Cipta Mandiri, 2024)
This research aims to determine the effect of multicultural education on students' tolerance attitudes at UPT SPF SD Inpres Antang 1 Makasar City. This research is ex post facto research using a quantitative approach. The research took place at SD Inpres Antang 1 Makassar City. The sample in this study was all 31 class IV/B students, as for the Simple Random Sampling technique. The sampling data collection method used a questionnaire, with data analysis using SPSS 23.0. The results of the descriptive analysis of multicultural education are in the interval 41-61 or in the quite good category, while attitudes of tolerance are in the interval 62-82 or in the good category. The results of the inferential analysis show that there is an influence of multicultural education on attitudes of tolerance at UPT SPF SD Inpres Antang 1 Makassar City with a sig value of 0.002 <0.05. Based on the results of the research that has been carried out, it can be concluded that multicultural education influences attitudes of tolerance at UPT SPF SD Inpres Antang 1 Makassar City.